Pendampingan Masyarakat Dengan Mewujudkan Kesadaran Peran Orang Tua Tentang Pentingnya Belajar Dirumah Bukan Hanya Disekolah Warga Dusun Wungurejo Kasembon Malang - Afida Fitrotul Mu’afah; Siti Kalimah (LP3M IAIFA Kediri, 2020)
Children have personality potential according to parenting styles and environmental colors. As a parent, it has become an inevitability to be able to give the best for their children. Not only find the best school for children, but provide affection by helping children achieve their developmental tasks. One of the developmental tasks that need to be achieved is to know yourself and the environment. Children can get to know themselves and their environment through the play activities that are their world. Through play, one aspect that can be developed is the social-emotional aspect, including personality. The personality of a boy is identical to the side of masculinity, while a girl's is synonymous with the femininity side. Boys who are only accustomed to developing their masculinity and girls who are only conditioned to cultivate their femininity side are feared to grow into a lame and overly rigid person. Efforts to prevent the growth of a lame and too rigid personality can be done by conditioning the child to have a person who is androgynius, namely a person who has a tendency to balanced nature.